The old open cluster Trumpler 5: a reddened, metal-poor, anticentre cluster - Piatti, Andres Eduardo (2004)
CCD observations in the Johnson V, Kron–Cousins I and the Washington system C and T1 passbands have been used to generate colour–magnitude diagrams (CMDs) reaching down to V ∼ 21.0 mag and T1 ∼ 19.0 for Trumpler 5, an old open cluster located towards the Galactic anticentre. Our data analysis confirms the existence of non-uniform extinction over the face of the cluster, the mean E(V − I) and E(C − T1) values being 0.80 ± 0.05 and 1.17 ± 0.15, respectively. Through comparison of the cluster CMDs with theoretical isochrones of the Geneva group, Washington Standard Giant Branches and measures of δV and δT1 indices, we derive the following values for the cluster apparent distance modulus, age, and metallicity: V − MV = 13.80 ± 0.30 (corresponding to a distance from the Sun of 2.4 ± 0.5 kpc and 0.04 kpc above the Galactic plane), t = 5.0 ± 0.5 Gyr and [Fe/H] = −0.30 ± 0.15. We estimate the cluster angular radius to be about 7.7 arcmin (= 5.4 pc) from star counts carried out within and outside the cluster field.